Time Efficiency And Quality Of Section 8 ECRL Project Based On New Austrian Tunneling Method (NATM) - Muhammad Nazif Aiman Mohamed Izamshah,; Joewono Prasetijo,; Azrul Nizam Ahmad, (Progress in Engineering Application and Technology, 2025)
The East Coast Rail Link (ECRL) is a major infrastructure initiative aimed at improving connectivity between the east and west coasts of Peninsular Malaysia through modern railway technology. One of the tunneling methods used in the project is the New Austrian Tunneling Method (NATM). However, there is limited research analyzing the relationship between time efficiency and quality in NATM applications. This study focuses on identifying factors that influence time efficiency in NATM within the ECRL project, determining time efficiency based on NATM implementation, and exploring the correlation between time efficiency and construction quality. The research relies on secondary data from ECRL documentation, including the Detailed Implementation Program (DIP), actual tunneling progress records, Non-Conformance Reports (NCR), and quality inspection reports. These data sources are used to evaluate time efficiency and analyze tunnel construction quality. Data were processed using Microsoft Excel to compare planned and actual excavation progress, calculate productivity rates, and generate time efficiency ratios and graphs. Quality measures were assessed by analyzing the number of NCRs and results from quality inspections. The study revealed a correlation between time efficiency and tunnel quality, as variations in time efficiency corresponded with the frequency of NCRs issued. Overall, the research provides a detailed assessment of how time efficiency in NATM tunnel construction impacts construction quality. The findings offer valuable insights that can support future project planning, enhance productivity, and improve overall quality control in similar tunneling projects across Malaysia and beyond.